PENGARUH PENGGUNAAN LIMBAH PADAT TAHU TERHADAP PERTUMBUHAN TANAMAN BAWANG MERAH (Allium cepa L) - Emiliana Mefita Bu’ulolo; Murnihati Sarumaha; Adam Smith Bago (Universitas Nias Raya, 2020)
The problem of this research is whether there is an effect of using solid waste tofu on the growth of shallot (Allium cepa L). The purpose of this study was to determine the effect of using solid waste tofu on the growth of shallot (Allium cepa L). This type of research is a quantitative research with a pure experimental method (true experiment) with a completely randomized design (CRD). The population of this study was red onion (Allnum cepa E) with 20 polybags and the sample of this study used simple random sampling consisting of 20 polybags of shallot plants (Allnm cepa L) with five treatments and four replications. The treatments applied were PO (without waste), PI (100 gr), P2 (200 gr), P3 (300 gr), P4 (400 gr). The data in this study were analyzed using the SPSS version 20 application. Based on the analysis using the one way ANOVA test, it showed that the administration of solid waste tofu in the P4 treatment (400 gr) on shallots (Allium cepa L) had a very significant effect on plant height, number of strands. leaves, and scallion length. The results of data analysis from Duncan's Least Significant Difference (BNT) test also found that the value of Fitung > Fubat means that HO is rejected and Ha is accepted. This is because the more doses of tofu solid waste given, the more nitrogen contained in tofu solid waste is received by the soil. The conclusion shows that the use of tofu solid waste on the growth of shallot (Allium cepa L) can affect the growth process of shallot plants. Researchers suggest, for the community, especially for farmers, it is better to use organic fertilizers and for advanced researchers, as a source of information for future researchers in conducting research.